Challenging misconceptions about clinical ethics support during COVID-19 and beyond: a legal update and future considerations. Issue 8 (21st April 2021) - Brierley, Joe; Archard, David; Cave, Emma
Abstract : The pace of change and, indeed, the sheer number of clinical ethics committees (not to be confused with research ethics committees) has accelerated during the COVID-19 pandemic. Committees were formed to support healthcare professionals and to operationalise, interpret and compensate for gaps in national and professional guidance. But as the role of clinical ethics support becomes more prominent and visible, it becomes ever more important to address gaps in the support structure and misconceptions as to role and remit. The recent case of Great Ormond Street Hospital for Children NHS Foundation Trust v MX, FX and X ([2020] EWHC 1958 (Fam), [21]–[23] and [58]) has highlighted the importance of patient/family representation at clinical ethics committee meetings. The court viewed these meetings as making decisions about such treatment. We argue that this misunderstands the role of ethics support, with treatment decisions remaining with the clinical team and those providing their consent. The considered review by clinical ethics committees of the moral issues surrounding complex treatment decisions is not a matter of determining a single ethical course of action. In this article, we consider current legal understandings of clinical ethics committees, explore current concepts of ethics support and suggest how they may evolve, considering the various mechanisms of the inclusion of patients and their representatives in ethics meetings which is not standard in the UK.